2017
DOI: 10.1371/journal.pone.0187434
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4, a glucagon-like peptide-1 analogue accelerates healing of chronic gastric ulcer in diabetic rats

Abstract: BackgroundDiabetes mellitus is an independent risk factor for impaired healing of peptic ulcers, and there are currently no supplementary therapeutics other than the standard antipeptic medicine to improve the ulcer healing in diabetes. This study examined the potential pleiotropic effect of a glucagon-like peptide (Glp)-1 analogue exendin (Ex)-4 on the regeneration of gastric ulcer in streptozotocin-induced diabetic rats.Methods and resultsChronic ulcer was created in rat stomach by submucosal injection of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In this study, treatment of gastric ulcer rats with Aloe barbadensis leaf extract led to significant and dose-dependent reduction in gastric tissue MDA level, an indication that the gastroprotective effect of the extract was exerted via suppression of lipid peroxidation in gastric mucosa. Reduced MDA level may in turn inhibit inflammation [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, treatment of gastric ulcer rats with Aloe barbadensis leaf extract led to significant and dose-dependent reduction in gastric tissue MDA level, an indication that the gastroprotective effect of the extract was exerted via suppression of lipid peroxidation in gastric mucosa. Reduced MDA level may in turn inhibit inflammation [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the so‐called ‘reparative lineages’ in the gut (Gouyer et al, 2010), the mucous neck cells of the gastric corpus produce mucins (MUC6 and MUC1, Hanby et al, 1999; Gouyer et al, 2010) and growth factors (TFF1, TFF2 and EGF proteins, Gouyer et al, 2010), which are believed to protect the other glandular cells from the acid secreted by neighbouring parietal cells. In accordance, Chen et al recently showed that administration of the GLP‐1 receptor agonist, exendin‐4, accelerated healing of stomach ulcers in diabetic rats (Chen et al, 2017). The strong tdTomato signal in Brunner's glands, which was confirmed by IHC (Baggio et al, 2018; Hepprich et al, 2020; Pyke et al, 2014) and quantitative polymerase chain reaction (qPCR) (Bang‐Berthelsen et al, 2016), is in accordance with earlier findings in humans and monkeys (Orskov & Poulsen, 1991; Qu et al, 2008), and functional studies in mice have shown that liraglutide causes an upregulation of genes in Brunner's glands associated with protection of the intestinal epithelial layer (Glass et al, 2017).…”
Section: Functional Significance Of Gi Expression Of the Receptormentioning
confidence: 63%
“…In further support of these observations, the suppressive effects of intraperitoneal injections of GLP‐1 on food intake and blood glucose levels were attenuated by complete sub‐diaphragmatic vagal de‐afferentation in rats (Hayes et al, 2011), indicating that these systemic effects are mediated in part through activation of GLP‐1 receptors on the vagal afferent nerve terminals. In accordance, intraperitoneal administration of 125 I‐exendin (Billeschou et al, 2021; Billing et al, 2018, 2019; Billings et al, 2018; Brookes et al, 2013; Brubaker, 2018; Bucinskaite et al, 2009; Buckley et al, 2019; Buhl et al, 1988; Canfora et al, 2017; Chen et al, 2017; Christiansen et al, 2018; Christiansen et al, 2019; Daniel et al, 2002; Day et al, 2009; de Heer et al, 2007; Deacon et al, 1995; Drucker & Yusta, 2014; Eissele et al, 1990, 1992; Fehmann et al, 1995; Friis‐Hansen et al, 2001; Gabery et al, 2020; Gasbjerg et al, 2019; Glass et al, 2017; Gouyer et al, 2010; Hanby et al, 1999; Hansen et al, 1999, 2015; Hayes et al, 2011) resulted in labelling of myenteric ganglia of the distal ileum, thus supporting the interpretation of experiments involving intraperitoneal administration of GLP‐1 to reflect interactions with nerve fibres within the myenteric plexus (Hayes et al, 2011).…”
Section: Functional Significance Of Gi Expression Of the Receptormentioning
confidence: 86%
See 1 more Smart Citation
“…These features are found to confine the progression of ulcers and accelerate the healing. 33 Anti-cancer effect of Ex-4 T2DM has been shown to predispose the risk of many malignancies, such as colon and breast and other cancer types. 37,38 Previous data demonstrated the anti-cancer properties of Ex-4 on cancer cell types such as breast cancer cells.…”
Section: Effect Of Ex-4 On Epitheliogenesis and Cutaneous Woundsmentioning
confidence: 99%